Kepemimpinan dan Praktek Total Quality Management terhadap Kinerja Perbankan Syariah di Kota Makassar - Alam, Syamsul; Hasbiyadi, Hasbiyadi (Sam Ratulangi University, 2021)
This study aims to analyze: (1) the influence of leadership on banking performance, (2) the effect of TQM practices on banking performance, (3) the influence of leadership and TQM on the performance of Islamic banking in Makassar City. This research is quantitative. The population of this research is all permanent employees in Islamic banks as many as 265 employees with a sample of 60 respondents. The data were collected using questionnaires and interviews, the sampling technique was simple random sampling, while the data analysis was carried out using multiple linear regression analysis. The results of the study at the 5% significance level indicate that: 1) leadership has a positive and significant effect on banking performance, as indicated by a regression coefficient of 0.234, sig 0.044. 2) TQM has a positive and significant effect on banking performance, this is indicated by the regression coefficient of 0.455, a sig value 0.000. 3) Leadership and TQM simultaneously have a positive and significant effect on the performance of Islamic banks in Makassar City where the coefficient of determination (R2) is 0.264 or 26.40%.